Shopee-Pay as an Electronic Transaction Instrument: A Maqāṣid al-Sharīʿah Perspective - Okta Prinoza; Wargo; Zaenal Abidin (Zabags International Journal of Islamic Studies, 2025)
The rapid expansion of financial technology in Indonesia has reshaped everyday transaction patterns, notably through digital wallets and paylater services offered by e-commerce platforms such as Shopee. While these services deliver convenience, efficiency, and broader accessibility, questions remain regarding their alignment with the principles of maqāṣid al-Sharīʿah, particularly the protection of wealth and the prevention of consumer harm. This study analyzes the transaction mechanics of ShopeePay and evaluates their conformity with maqāṣid al-Sharīʿah. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, observation, and documentation, and validated via triangulation. Findings indicate that ShopeePay, as an electronic payment instrument, is perceived as efficient, secure, and supportive of financial inclusion; however, the Shopee PayLater feature introduces ethical concerns due to potential interest-like late fees and heightened risks of consumptive behavior. The study advances the Islamic fintech literature by underscoring the need to integrate maqāṣid al-Sharīʿah into assessments of digital financial services and offers practical implications for regulators and industry practitioners to design Sharia-compliant contractual models and strengthen ethics-driven digital financial literacy.